2010
DOI: 10.1016/j.gca.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Formation and geochemical significance of micrometallic aggregates including fissiogenic platinum group elements in the Oklo natural reactor, Gabon

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The use of the A = 101 isobar in combination with other isotopic markers has been key for developing an understanding of geological transformations and geochemical behaviours of different isotopes and radioisotopes that were formed in the Oklo natural fission reactor in Gabon. For example, one study on the micro-metallic and ε-phase aggregates, including the fission-derived elements Ru, Rh, Pd, Te, Pb, As, S, and Bi, were collected and the isotopic ratios of different isotopic systems, i.e., 235 U/ 238 U, 90 Zr/ 91 Zr, 95 Mo/ 97 Mo, and 99 Ru/ 101 Ru, were analysed 128 . Whereas the 90 Zr/ 91 Zr and 95 Mo/ 97 Mo ratios in the metallic aggregates varied little in composition, likely due to constant separate mixing of fissiogenic and non-fissiogenic components, the 99 Ru/ 101 Ru ratios exhibited large variations, which could not be described by such processes.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the A = 101 isobar in combination with other isotopic markers has been key for developing an understanding of geological transformations and geochemical behaviours of different isotopes and radioisotopes that were formed in the Oklo natural fission reactor in Gabon. For example, one study on the micro-metallic and ε-phase aggregates, including the fission-derived elements Ru, Rh, Pd, Te, Pb, As, S, and Bi, were collected and the isotopic ratios of different isotopic systems, i.e., 235 U/ 238 U, 90 Zr/ 91 Zr, 95 Mo/ 97 Mo, and 99 Ru/ 101 Ru, were analysed 128 . Whereas the 90 Zr/ 91 Zr and 95 Mo/ 97 Mo ratios in the metallic aggregates varied little in composition, likely due to constant separate mixing of fissiogenic and non-fissiogenic components, the 99 Ru/ 101 Ru ratios exhibited large variations, which could not be described by such processes.…”
Section: Applicationsmentioning
confidence: 99%
“…It is suggested that fractionation would have occurred over the timeframe of the t 1/2 of 99g Tc or ~2.11 × 10 5 y, where the leaching behaviour of Tc, said to be 10 3 –10 4 times that of Ru, would have been a strong driver of fractionation between the two elements. Likewise, the chemical fraction of Tc and Ru could have taken place during the incorporation of each into the metallic aggregate 128 . On the other hand, Groopman et al.…”
Section: Applicationsmentioning
confidence: 99%